Facile fabrication of 2D material multilayers and vdW heterostructures with multimodal microscopy and AFM characterization. (January 2022) - Dong, Siyan; Zhang, Xiang; Nathamgari, S. Shiva. P.; Krayev, Andrey; Zhang, Xu; Hwang, Jin Wook; Ajayan, Pulickel M.; Espinosa, Horacio D.
Graphical abstract: Abstract: Reliable transfer processes that enable manipulation of two-dimensional (2D) materials, e.g., transition metal dichalcogenides (TMDCs) and MXenes, from one substrate to another has been a necessity for successful device fabrication. With both mechanical exfoliation and chemical vapor deposition (CVD) widely used, a versatile, clean, deterministic, and yet simple transfer technique is highly needed. To address such need, we developed a transfer method that takes advantage of wettability contrast between interfaces without the use of sacrificial layers or chemical processes. More importantly, a setup was developed to carry out this transfer method with high sample selectivity and fine control of the position and orientation of transferred TMDC crystals, a feature required for fabrication of the devices based on vertical 2D heterostructures. Using both exfoliated and CVD grown materials and subsequent atomic force microscopy (AFM), photoluminescence (PL), confocal Raman and tip enhanced Raman spectroscopy (TERS) characterization, we ascertained the quality of interfaces resulting from the transfer process while preserving excellent 2D material integrity. PL and TERS maps revealed nanometer-scale heterogeneities in the interfaces of fabricated heterostructures, which should enable further perfection of the transfer technique. TERS/TEPL information were employed to identify areas suitable for nanodevice fabrication, making the reported transfer and characterization methods ideal for making high quality assembly of 2D heterostructure more accessible, which should facilitate exploration of vertical 2D heterostructures for applications in electronics, batteries, solar cells, and twistronics.